2008
DOI: 10.1096/fj.08-111203
|View full text |Cite
|
Sign up to set email alerts
|

Directed induction of anterior and posterior primitive streak by Wnt from embryonic stem cells cultured in a chemically defined serum‐free medium

Abstract: Formation of the primitive streak (PS) is the initial specification step that generates all the mesodermal and endodermal tissue lineages during early differentiation. Thus, a therapeutically compatible and efficient method for differentiation of the PS is crucial for regenerative medicine. In this study, we developed chemically defined serum-free culture conditions for the differentiation of embryonic stem (ES) cells into the PS-like cells. Cultures supplemented with Wnt showed induction of expression of a PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 37 publications
2
67
1
Order By: Relevance
“…This affirms the findings of prior reports demonstrating that mesodermal and endodermal cell fates are determined by a delicate time-and dose-dependent balance of Wnt, activin, BMP, and FGF signaling. 24,25,47,[50][51][52][53][54][55][56][57][58][59][60][61][62] Our findings, however, contrast with those of a recent study by Tan and colleagues, who showed that prolonged exposure to GSK-3b inhibition, specifically with CHIR, promoted an endodermal rather than mesodermal fate. 49 With our differentiation conditions, definitive endoderm differentiation could be achieved only with the synergistic effect of CHIR and high-dose activin.…”
Section: Mixl1contrasting
confidence: 99%
“…This affirms the findings of prior reports demonstrating that mesodermal and endodermal cell fates are determined by a delicate time-and dose-dependent balance of Wnt, activin, BMP, and FGF signaling. 24,25,47,[50][51][52][53][54][55][56][57][58][59][60][61][62] Our findings, however, contrast with those of a recent study by Tan and colleagues, who showed that prolonged exposure to GSK-3b inhibition, specifically with CHIR, promoted an endodermal rather than mesodermal fate. 49 With our differentiation conditions, definitive endoderm differentiation could be achieved only with the synergistic effect of CHIR and high-dose activin.…”
Section: Mixl1contrasting
confidence: 99%
“…Similar to the Xenopus organizer, it seems that both TGFb and WNT pathways have a crucial role in mouse organizer formation [16][17][18][19][20]. To test whether these two pathways affect the establishment of the human gastrula organizer, hESCs were harvested and allowed to aggregate into EBs in the presence of Activin A and LiCl, activators of the TGFb [21] and WNT [22] pathways, respectively.…”
Section: Tgfb and Wnt Pathways Induce Differentiating Hescs To Expresmentioning
confidence: 99%
“…In studies addressing this challenge, two strategies have emerged. One involves exogenously controlling differentiation by delivering factors that are known or thought to be involved in specification, commitment and proliferation of the cell type of interest (Laflamme, Chen et al 2007;Pick, Azzola et al 2007;Yang, Soonpaa et al 2008;Nakanishi, Kurisaki et al 2009). The second strategy focuses on controlling physical parameters of aggregate formation, such as aggregate size and shape (Ng, Davis et al 2005;Khademhosseini, Ferreira et al 2006;Mohr, de Pablo et al 2006;Burridge, Anderson et al 2007;Pick, Azzola et al 2007;Bauwens, Peerani et al 2008;Ungrin, Joshi et al 2008;Niebruegge, Bauwens et al 2009).…”
Section: Introductionmentioning
confidence: 99%